Cooperative interactions between p53 and NFκB enhance cell plasticity - Bisio, Alessandra (Oncotarget, 2014)
The p53 and NFκB sequence-specific transcription factors play crucial roles in cell proliferation and survival with critical, even if typically opposite, effects on cancer progression. To investigate a possible crosstalk between p53 and NFκB driven by chemotherapy-induced responses in the context of an inflammatory microenvironment, we performed a proof of concept study using MCF7 cells. Transcriptome analyses upon single or combined treatments with doxorubicin (Doxo, 1.5μM) and the NFκB inducer TNF-alpha (TNF⍺, 5ng/ml) revealed 432 up-regulated (log(2) FC> 2), and 390 repressed genes (log(2) FC< -2) for the Doxo+TNF⍺ treatment. 239 up-regulated and 161 repressed genes were synergistically regulated by the double treatment. Annotation and pathway analyses of Doxo+TNF⍺ selectively up-regulated genes indicated strong enrichment for cell migration terms. A panel of genes was examined by qPCR coupled to p53 activation by Doxo, 5-Fluoruracil and Nutlin-3a, or to p53 or NFκB inhibition. Transcriptome data were confirmed for 12 of 15 selected genes and seven (PLK3, LAMP3, ETV7, UNC5B, NTN1, DUSP5, SNAI1) were synergistically up-regulated after Doxo+TNF⍺ and dependent both on p53 and NFκB. Migration assays consistently showed an increase in motility for MCF7 cells upon Doxo+TNF⍺. A signature of 29 Doxo+TNF⍺ highly synergistic genes exhibited prognostic value for luminal breast cancer patients, with adverse outcome correlating with higher relative expression. We propose that the crosstalk between p53 and NFκB can lead to the activation of specific gene expression programs that may impact on cancer phenotypes and potentially modify the efficacy of cancer therapy.